Drinking water supply and sanitation services on the threshold of the XXI century - Jouravlev, Andrei (ECLAC SantiagoCL, 2004)
Analyzes the status of drinking water supply and sanitation services in the countries of Latin America and the Caribbean at the beginning of the twenty-first century.